The Voice and Memory of Land in Woody Guthrie's songs - Moravec, Jan (Univerzita Pardubice, 2022)
The work deals with the portrayal of historical events in the songs of Woody Guthrie. It focuses on the period between the 1930s and 1950s. The objects of research are cultural and political references in the songs of Woody Guthrie. The work focuses on the role of the singer as a voice and memory of the nation.
Hlas a paměť národa v písňové tvorbě Woody Guthrieho
Keywords: tradiční folková hudba; skladatelé; písňové texty; folkoví zpěváci; traditional folk music; songwriters; song lyrics; folk singers